2012
DOI: 10.1590/s1983-40632012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Potássio no desenvolvimento inicial da soqueira de cana crua

Abstract: Na colheita mecanizada sem o uso de fogo ocorre deposição de palhada na superfície do solo, a qual pode ser reciclada e reduzir a adubação potássica para a cana-de-açúcar, em relação à cana queimada, o que pode refletir em menor custo de produção. Objetivou-se avaliar o efeito da aplicação de potássio no desenvolvimento inicial da soqueira de primeiro corte da cana-de-açúcar (variedade SP 89-1115), em sistema de colheita sem despalha a fogo. O experimento foi instalado em uma área de primeira soqueira de cana-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
1
9
0
8
Order By: Relevance
“…But at the second ratoon, the application of K fertilizer caused increments with linear adjustment in soil K content at depths 20-40 cm, reaching 0.07 cmolc kg -1 with the highest nutrient rate (Figure 2b). Results are similar to those reported by Silva (2010) and Flores et al (2012).…”
Section: Resultssupporting
confidence: 93%
“…But at the second ratoon, the application of K fertilizer caused increments with linear adjustment in soil K content at depths 20-40 cm, reaching 0.07 cmolc kg -1 with the highest nutrient rate (Figure 2b). Results are similar to those reported by Silva (2010) and Flores et al (2012).…”
Section: Resultssupporting
confidence: 93%
“…The significantly different K + concentrations denote their proportional response to K 2 O application, mainly considering the K + increases in the soil solution between 105 and 122 DAP (sprouting and establishment stages). Flores et al (2012) evaluated the K + distribution in soils under sugarcane crops and found similar results, with K 2 O applications affecting the K + concentration in the soil solution of the surface layer the K + concentration in the soil solution increased in the 0.0-0.2 m layer as the K 2 O rates were increased.…”
Section: Source Of Variationmentioning
confidence: 69%
“…Based on studies about soil fertilization for sugarcane crops (ANDRADE JÚNIOR et al, 2010;COELHO et al, 2014;FLORES et al, 2012;JORIS, 2015), five treatments were established, composed of N (urea) + K 2 O (potassium chloride) at rates of 60+120 (T1); 180+120 (T2); 120+60 (T3); 120+180 (T4), and 120+120 (T5) kg ha -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The K leaching is significant in sandy soils, which are characterized by having low effective CEC and low water retention capacity (Ernani et al, 2007). Furthermore, high rainfall rates may enable the displacement of K in the soil profile, reducing the levels of this nutrient in the surface layers, even in more clayey soils and with high CEC (Flores et al, 2012).…”
Section: Resultsmentioning
confidence: 99%